Combined fertilization with nitrogen-potassium to mitigate salt stress in okra - Barros Sales, Giuliana Naiara; Maria de Souza Silva Neta, Alzira; Bezerra da Costa, Franciscleudo; Soares de Lima, Geovani; Souto Ribeiro, Wellington; Silva, Toshik Iarley da; de Medeiros Lima, Brencarla; Esfrain Pereira, Walter (Comunicata Scientiae, 2023)
Okra (Abelmoschus esculentus) is sensitive to the salinity of water and soil, a common abiotic stress in the semi-arid region of northeastern Brazil; however, such sensitivity is variable with water management in the soil-plant-atmosphere system. Thus, the objective was to evaluate the fertilization with nitrogen-potassium combinations in okra cultivated under salt stress. Photosynthetic pigments, gas exchange, growth and fruit quality were evaluated. Fertilization with N1:K1 (40% N + 40% K2O) reduced the damage caused by salt stress and increased the chlorophyll contents, while the application of N4:K4 (130% N + 100% K2O) decreased the damage caused by salt stress and increased the carotenoid contents. The combination of N:K fertilization did not affect gas exchange, however, salt stress decreased these variables. Fertilization with N2:K2 (70% N + 60% K2O) reduced the damage caused by salt stress and increased the leaf area of okra. In addition, salt stress decreased the number of fruits and increased the fresh mass of okra fruits. The N:K fertilization also reduced the damage caused by salt stress and in the soluble solids content, titratable acidity, SS/TA ratio, and ascorbic acid content. Thus, N:K fertilization can be seen as an important agronomic strategy to improve the performance of okra quality subjected to saline conditions.